2014
DOI: 10.1242/dev.103218
|View full text |Cite
|
Sign up to set email alerts
|

Fascin links Btl/FGFR signalling to the actin cytoskeleton during Drosophila tracheal morphogenesis

Abstract: A key challenge in normal development and in disease is to elucidate the mechanisms of cell migration. Here we approach this question using the tracheal system of Drosophila as a model. Tracheal cell migration requires the Breathless/FGFR pathway; however, how the pathway induces migration remains poorly understood. We find that the Breathless pathway upregulates singed at the tip of tracheal branches, and that this regulation is functionally relevant. singed encodes Drosophila Fascin, which belongs to a conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 52 publications
2
40
0
Order By: Relevance
“…A number of cytoskeleton-organizing molecules have been described as critical regulators of subcellular tube formation, tube stabilization and branching of terminal tracheal cells [35], [63], [76], [79][81].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of cytoskeleton-organizing molecules have been described as critical regulators of subcellular tube formation, tube stabilization and branching of terminal tracheal cells [35], [63], [76], [79][81].…”
Section: Discussionmentioning
confidence: 99%
“…This involves actin organization in filopodia at the migrating fronts of the embryonic terminal cells [63]. Singed is also transcriptionally upregulated by Btl in terminal cells [63].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Live imaging has revealed that Bnl induces tip cells to undergo cytoskeletal reorganization, enriching actin at their basal surface (Lebreton and Casanova, 2014). Bnl also induces the activation of Rac and the expression of fascin, an actin-bundling protein required for the formation of filopodia at the leading edge (Okenve-Ramos and Llimargas, 2014). By contrast, the trailing stalk cells exhibit high levels of actin at their apical surfaces (Lebreton and Casanova, 2014).…”
Section: Invasive Branchingmentioning
confidence: 99%
“…Also absent from T1 EW (Table S2) was a wing-specific isoform of salimus (sls), a gene involved in muscle development and attachment (27)(28)(29) that in Drosophila is coexpressed with trh in ventral-origin cells. Another tracheal morphogenesis gene, forked (f) (30), involved in formation of mechanosensory wing bristles (31), was among the wing-specific genes missing from T1 EW. Additional trh-regulated genes (vvl, spalt, and Stat92E) (26) and the ventral-origin wing specification gene nubbin (nub) (32) were detectable but reduced in T1 EW compared with T2 wing (P = 0.0001; mean difference > twofold) (Fig.…”
Section: Insights About Wing Origins and Functionalization From T1 Ecmentioning
confidence: 99%